The Effect of Contributed Capital Mix on Dividend Policy: Testing Life Cycle Theory in The Covid-19 Pandemic Era - Prayanthi, Ika; Rantung, Danny Ivan; Oroh, Nouke Sysca (RGSA : Revista de Gestão Social e Ambiental, 2024)
Objective: This study aims to test whether life cycle theory is relevant in the era of the Covid-19 pandemic crisis. Specifically, whether the contributed capital mix has a significant effect on dividend policy.